A review of the potential of smart homes to support independent living - Fox, Caroline; Rodrigues, Lucélia Taranto; Altomonte, Sergio; Gillott, Mark C. (2017)
Between 2015 and 2050, the proportion of the world's population over 60 years of age is expected to nearly double, from 12% to 22%. Whilst hospitals offer care to people with health problems, support at home is generally limited to carers, a costly labour intensive method that impacts on the ability of many elderly patients to live independently. This pushes the demand for housing that caters for elderly people allowing them to remain in their homes but with some level of healthcare support. In the UK, the domestic sector currently accounts for around 30% of total energy consumption and contributes in the region of 27% of total carbon dioxide and greenhouse gas emissions. With an ageing population, offering healthy environments with a cushion against rising energy prices will be essential for people spending most of their time at home and often living on limited budgets. In this context, the drive to reduce energy consumption and associated greenhouse gas emissions from housing has acted as a catalyst in the increasing installation of meters and sensors for monitoring energy use and indoor environmental conditions in buildings. These monitoring technologies can track and record a range of parameters such as temperature, air quality, occupant behaviour etc. Many of these could be optimised to help create environments that assist people such as the elderly to live at home.